PRAKTIK SEWA MENYEWA POHON JERUK DI DESA PANDANSARI KECAMATAN PONCOKUSUMO KABUPATEN MALANG PERSPEKTIF AKAD IJARAH - M. Ainun Wakhit; Rudi Hermawan (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
This study discussed the practice of renting orange trees in Pandansari Village, Poncokusumo District, Malang Regency, viewed from the perspective of the ijarah contract in Islamic law. This practice had been going on for generations, but it caused problems such as unclear contracts, uncertainty of harvest results, and agreements that are only made verbally. The method used was qualitative descriptive with a normative approach. Data were collected through interviews with orange orchard owners and tenants, as well as community leaders, then analyzed based on the principles of the ijarah contract according to Islam. The results of the study indicated that the practice of renting in the village is not fully in accordance with the ijarah contract. The object of the lease was the harvest (fruit), not the benefits of the tree, and there was an element of uncertainty (gharar) that can harm the tenant. In addition, all risks were borne by the tenant and there was no written agreement. Therefore, this contract was more appropriate if replaced with a musaqah or muzara'ah contract that was in accordance with sharia and was fair for both parties.